2016
DOI: 10.1097/md.0000000000004748
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of tuberculosis on patients with occupational lung diseases

Abstract: Occupational lung diseases are well recognized risk factors for tuberculosis (TB). However, little research investigated the effect of TB on the clinical course and outcome of occupational lung diseases.We conducted a 13-year observational study of a nationwide cohort to evaluate the risk and prognosis of TB among patients with occupational lung diseases in Taiwan.By using the Taiwan National Health Insurance database, occupational lung diseases cohort was identified according to diagnosis codes from 1998 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Even after the patient is no longer exposed to silica dust, the impairment of lung function still keeps progressing. In particular, low‐aged or acute silicosis could increase the risk of pulmonary tuberculosis, which would result in poor prognostic outcome of pneumoconiosis with high aggravation rate and fatality rate . According to "China Occupational Exposure Limits for Hazardous Factors in Workplace," the upper limit of the total dust concentration (free SiO 2 content <10%) is 4 mg/m 3 , and the upper limit of respirable dust concentration is 1.5 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even after the patient is no longer exposed to silica dust, the impairment of lung function still keeps progressing. In particular, low‐aged or acute silicosis could increase the risk of pulmonary tuberculosis, which would result in poor prognostic outcome of pneumoconiosis with high aggravation rate and fatality rate . According to "China Occupational Exposure Limits for Hazardous Factors in Workplace," the upper limit of the total dust concentration (free SiO 2 content <10%) is 4 mg/m 3 , and the upper limit of respirable dust concentration is 1.5 mg/m 3 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, low-aged or acute silicosis could increase the risk of pulmonary tuberculosis, 19 which would result in poor prognostic outcome of pneumoconiosis with high aggravation rate and fatality rate. 20 According to "China Occupational Exposure Limits for Hazardous Factors in Workplace," the upper limit of the total dust concentration (free SiO 2 content <10%) is 4 mg/m 3 , and the upper limit of respirable dust concentration is 1.5 mg/m 3 . An investigation of 36 cement manufacturing enterprises in 2013 reported that the dust concentration exceeded the national limit in 86% enterprises.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a very common disease worldwide, although the prevalence in most Western countries is low [ 41 ]. It has been shown that patients with pneumoconiosis are at an especially high risk to develop active tuberculosis, and this is associated with worse survival [ 37 , 38 ]. In patients with IPF, the prevalence of active tuberculosis seems to be higher than in the general population, and this might also be associated with worse survival [ 39 ].…”
Section: Application Of the ‘Treatable Traits’ Concept In Fibrotic Ildmentioning
confidence: 99%
“…Sputum culture conversion is widely used to determine bacteriological response to anti-TB therapy and is associated with long-term cure [3]. According to recent reports, cigarette smoking is related to delayed culture conversion and treatment failure [4][5][6]. However, the relationship between actual smoking-related lung damage and pulmonary TB (PTB) is still unknown.…”
Section: Read Full Licensementioning
confidence: 99%